Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1300/j069v14n04_09
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Alternative Treatments for Homeless Substance-Abusing Men:

Abstract: The present study was designed to explore the relative efficacy of three types of service delivery intervention models for homeless men with alcohol and/or drug problems: integrated comprehensive residential services provided at one site (Group 1); on-site shelter-based intensive case management with referrals to a community network of services (Group 2); and usual care shelter services with case management (Group 3). In addition to assessing the relative efficacy of these approaches in terms of drug and alcoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
52
0
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 10 publications
0
52
0
2
Order By: Relevance
“…Providing direct housing assistance seems to help. Other potential treatment modalities include case management and integrated models of care (15,16). Other potential treatment modalities include case management and integrated models of care (15,16).…”
mentioning
confidence: 99%
“…Providing direct housing assistance seems to help. Other potential treatment modalities include case management and integrated models of care (15,16). Other potential treatment modalities include case management and integrated models of care (15,16).…”
mentioning
confidence: 99%
“…Limited options for treatment and a mistrust of the system can hamper recovery efforts (Littrell & Beck, 2001), as can cultural bias and culturalbound resistance to treatment (Landrine, 1992). Studies have shown that the more socially isolated a person is, the more likely he or she is to experience negative outcomes (Stahler, Shipley, Bartelt, DuCette , & Shandler, 1995). Structured social support functions not only to unite individuals in a common social network, but also to provide them with positive social influence.…”
Section: Peer Support and Recovery Communitiesmentioning
confidence: 99%
“…Aftercare appears to be critical for the long-term continuation of gains obtained in treatment (Mutmne, 1991;Stahler, Shipley, Bartelt, & DuCette, 1995 and a monthly "alumnac" group. After completing one year of outpatient counseling, there is a graduation ceremony that involves a certificate; the presentation of flowers to the women from their counselors; and an opportunity for the Hutchinson Place staff, the woman's family, and friends to speak about the women's achievement.…”
Section: Residential Treatmentmentioning
confidence: 99%
“…Although there have been relatively few drug treatment programs designed especially to serve the special needs of the homeless (for some notable exceptions see Conrad et al, 1993;Stahler, 1995;Argeriou & McCarty, 1990), even fewer have been targeted to homeless women with children (Elder et al, 1994;Smith, North, & Fox, 1995;Robertson, 1991). Many of these women come from alcoholic or addictive families of origin; experienced early and continuing physical, emotional and sexual abuse; suffer from sexually transmitted diseases including HIV; experience depression; have endured racial discrimination; and tend to have little chance of obtaining long-term, safe, independent, and affordable housing.…”
Section: Introductionmentioning
confidence: 99%